2020
DOI: 10.1136/bjophthalmol-2020-315933
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity outcomes and anti-VEGF therapy intensity in diabetic macular oedema: a real-world analysis of 28 658 patient eyes

Abstract: Background/AimTo assess visual acuity (VA) outcomes and antivascular endothelial growth factor (anti-VEGF) treatment intensity in diabetic macular oedema (DMO).MethodsRetrospective analysis was performed in treatment-naïve patients with DMO from 2013 to 2018 using a database of aggregated de-identified electronic medical records (Vestrum Health).ResultsAt 1 year, 28 658 patient eyes underwent a mean of 6.4 anti-VEGF injections, gaining a mean of +4.2 letters (95% confidence interval for mean gain: +4.0 to +4.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 20 publications
4
90
0
3
Order By: Relevance
“…4 Similarly, a recent real-world study with corresponding eligibility criteria in 28 658 patient eyes with DME demonstrated a mean gain of 4.2 letters after a mean of 6.4 anti-VEGF injections in 1 year. 5 Nonetheless, while real-world patients with RVO-related ME show greater 1-year visual gains than real-world patients with nAMD and DME, they experience a larger gap in visual gain when compared with corresponding RCTs. In particular, for BRVO-related and CRVO-related ME, the aforementioned registration trials demonstrate an average 1-year BCVA improvement of 17.7 letters and 15.7 letters, respectively.…”
Section: Real-world Patients With Rvo-related Me Receive Fewer Anti-vmentioning
confidence: 90%
See 3 more Smart Citations
“…4 Similarly, a recent real-world study with corresponding eligibility criteria in 28 658 patient eyes with DME demonstrated a mean gain of 4.2 letters after a mean of 6.4 anti-VEGF injections in 1 year. 5 Nonetheless, while real-world patients with RVO-related ME show greater 1-year visual gains than real-world patients with nAMD and DME, they experience a larger gap in visual gain when compared with corresponding RCTs. In particular, for BRVO-related and CRVO-related ME, the aforementioned registration trials demonstrate an average 1-year BCVA improvement of 17.7 letters and 15.7 letters, respectively.…”
Section: Real-world Patients With Rvo-related Me Receive Fewer Anti-vmentioning
confidence: 90%
“…Analysis methods were similar to previous studies, which facilitated comparison of anti-VEGF treatment outcomes in RVOrelated ME with those previously described in other disease states using the same database. [2][3][4][5] Outcomes were analysed at the patient eye level, separately for branch retinal vein occlusion (BRVO)related ME and central retinal vein occlusion (CRVO)-related ME. As a sensitivity analysis, main outcome measures were assessed, excluding patients with RVO-related ME who underwent bilateral anti-VEGF treatment during the study period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, patients with DME experienced a mean 1-year BCVA gain of approximately +5 letters in a clinical setting, while in the DRCR.net Protocol T trial, vision improved by a mean of +13.3, +9.7 and +11.2 at 1 year for eyes treated with aflibercept, bevacizumab and ranibizumab, respectively. 9 , 19 , 80–82 …”
Section: Discussionmentioning
confidence: 99%